Role of circulating microparticles and cytokines in periodontitis associated with diabetes - Cassiano, Bárbara Adelungue; Silveira, Ana Luíza Pereira Assunção; Kim, Yeon Jung; do Amaral, Jônatas Bussador; da Silva Nali, Luiz Henrique; Bachi, André Luis Lacerda; Resende, Leonardo Diniz; Fonseca, Francisco Antonio Helfenstein; de Oliveira Izar, Maria Cristina; Tuleta, Izabela Dorota; Victor, Jefferson Russo; Pallos, Débora; et al. (Frontiers in Medicine, 2024)
Background Periodontitis is a chronic inflammatory condition that affects the supporting tissues of the teeth, and can lead to serious complications such as tooth loss and systemic health problems, including diabetes, which have a bidirectional relationship with periodontitis. Circulating microparticles originate from different cell types after stimuli such as activation or apoptosis. Interleukins are related to processes in the regulation of the immune response, inflammation, and cell growth. This study aimed to evaluate circulating microparticles as well as interleukins in the plasma, at baseline and 1 month after the end of the non-surgical periodontal treatment. Methods Samples were collected from 45 patients, with moderate to severe periodontitis with diabetes (N = 25) and without diabetes (N = 20). Microparticles were evaluated in the platelet-poor plasma by flow cytometer. Cytokine levels were evaluated by the enzyme immunoabsorption assay (ELISA). Results Higher levels of the pro-inflammatory cytokines were found in the group with diabetes compared to the non-diabetic group both at baseline and 1 month after the end of the treatment. A higher IL-6/IL-10 ratio was found in patients with diabetes compared to the group without diabetes at T0 and T1, whereas an increased IFN-γ/IL-10 ratio was only found at T1 in patients with diabetes in comparison to the group without diabetes. In the group with diabetes, it was verified positive correlations between IL-10 and IL-6 or IFN-γ and a negative correlation between IL-6 and PMP, at T0; in contrast, in the T1, negative correlations were found between TNF-α and IL-10 or PMP. Besides, at T0, it was evidenced positive correlations both between circulating TNF-α and IL-6, and IL-10 and EMP, as well as a negative correlation between IL-10 and PMP in the group with diabetes. In addition, it was observed in T1 positive correlations between levels of TNF-α and IL-6, IFN-γ, or IL-10, and between PMP and IFN-γ, and between EMP and IL-6, TNF-α and IFN-γ in this group. Conclusion The results suggest a modulatory effect of the periodontitis associated with diabetes, as well as the periodontal treatment, in the systemic inflammatory status of the participants of the study.